Understanding the Influence of Secondary Metabolites in Plant Invasion Strategies: A Comprehensive Review - Rasheed Akbar; Jianfan Sun; Yanwen Bo; Wajid Ali Khattak; Amir Abdullah Khan; Cheng Jin; Umar Zeb; Najeeb Ullah; Adeel Abbas; Wei Liu; Xiaoyan Wang; Shah Masaud Khan; et al. (Plants)
The invasion of non-native plant species presents a significant ecological challenge worldwide, impacting native ecosystems and biodiversity. These invasive plant species significantly affect the native ecosystem. The threat of invasive plant species having harmful effects on the natural ecosystem is a serious concern. Invasive plant species produce secondary metabolites, which not only help in growth and development but are also essential for the spread of these plant species. This review highlights the important functions of secondary metabolites in plant invasion, particularly their effect on allelopathy, defense system, interaction with micro soil biota, and competitive advantages. Secondary metabolites produced by invasive plant species play an important role by affecting allelopathic interactions and herbivory. They sometimes change the soil chemistry to make a viable condition for their proliferation. The secondary metabolites of invasive plant species inhibit the growth of native plant species by changing the resources available to them. Therefore, it is necessary to understand this complicated interaction between secondary metabolites and plant invasion. This review mainly summarizes all the known secondary metabolites of non-native plant species, emphasizing their significance for integrated weed management and research.